Development of thixotropic nanomaterial in fluid flow with gyrotactic microorganisms, activation energy, mixed convection. (April 2020) - Ijaz Khan, M.; Haq, Fazal; Khan, Sohail A.; Hayat, T.; Imran Khan, M.
Highlights: MHD flow of thixotropic nanomaterial with gyrotactic microorganisms is considered. Brownian and thermophoretic diffusion effects are accounted. Bio-convective flow is addressed. Binary chemical reaction with activation energy is discussed. Abstract: Background: In this article, impact of gyrotactic microorganisms on nonlinear mixed convective MHD flow of thixotropic nanoliquids is addressed. Effects of Brownian motion and thermophoresis diffusion are considered. Characteristics of heat and mass transfer are analyzed with activation energy, Joule heating and binary chemical reaction. Nonlinear PDE's are reduced to ordinary equation by using suitable transformations. Method: For convergent series solution the given system is solved by the implementation of the homotopic analysis technique (HAM). Results: Influences of different flow controlling variables on the velocity, microorganisms, concentration and temperature are examined through graphs. Surface drag force, density number, Sherwood number and gradient of temperature are examined versus different flow parameters through graphs. For larger thixotropic fluid parameters the velocity field boosts up. For rising values of Hartmann number the velocity and temperature have opposite behaviors.